Pemodelan Metode Elemen Hingga Balok Beton Bertulang dengan Perkuatan CFRP (Carbon Fiber Reinforced Polymer) yang Dikenai Lentur dan Geser - Rada, Stefanus; Aptiyasa, Putu A. A. (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2025)
Reinforced concrete beams as structural elements are designed to withstand working load. Expenses that exceed the capacity of the beam section, would result in the failure load bearing beams in flexure and shear. In this analysis, the beam with two point loading using CFRP (Carbon Fiber Reinforced Polymer) as reinforcement against bending and shear capacity.Modeling carried out by the three dimensional shape, using the Abaqus Student Edition program 6.14. There are three sections in the analysis is the eight point solid elements (beams), shell element (CFRP), and truss elements (reinforcement), using the concept of embedded elements and tie fuction. The steps that must be overcome in the process of analysis is pre processing, simulation and post-processing.The results of the analysis of Abaqus Student Edition 6.14 with experimental results performed by others, that the concrete beams reinforced by CFRP reinforcement subjected to bending and shear, did not show a significant difference in the difference in value. The beams are subjected to bending has a difference of values, namely: the type of R1 = 8,197%; R2 = 1,443%; R3 = 1,393%; EBR_M 1 layer = 4,360%; EBR_M 2 layers = 2,390%; and EBR_M 3 layers = 0,115%. While the beam is subjected to shear has a difference of values, namely: the type A10_R = 0,199%; A10_S = 22,055%; A10_M = 0,770%; A12_R = 0,429%; A12_S = 39,546%; A12_M = 21,421%; B10_R = 10,781%; and B12_R = 8,322%.